Double heterozygosity with mutations involving both the GJB2 and GJB6 genes is a possible, but very rare, cause of congenital deafness in the Czech population - Seeman, P; Bendová, O; Rasková, D; Malíková, M; Groh, D; Kabelka, Z (Annals of human genetics, 2005)
Mutations in the GJB2 gene are the most common cause of prelingual, autosomal recessive, sensorineural hearing loss worldwide. Nevertheless, 10% to 50% of patients with prelingual nonsyndromic deafness only carry one mutation in the GJB2 gene. Recently a large 342 kb deletion named Delta(GJB6-D13S1830) involving the GJB6 gene was reported in Spanish and French deafness patients, either in a homozygous state or in combination with a monoallelic GJB2 mutation. No data have been reported about the frequency of this mutation in central Europe. Thirteen Czech patients with prelingual nonsyndromic sensorineural deafness carrying only one pathogenic mutation in the GJB2 gene were tested for the presence of the Delta(GJB6-D13S1830) mutation. One patient with a GJB2 mutation (313del14) also carried the Delta(GJB6-D13S1830). This is the first reported Czech case, and probably also the first central European case, of prelingual deafness due to mutations involving both the GJB2 and GJB6 genes. In addition, the Delta(GJB6-D13S1830) was not detected in 600 control chromosomes from Czech individuals with normal hearing. We show that in the Czech Republic the Delta(GJB6-D13S1830) is not the second most common causal factor in deafness patients heterozygous for a single GJB2 mutation, and that Delta(GJB6-D13S1830) is very rare in central Europe compared to reports from Spain, France and Israel.
Keywords: Humans; Case-Control Studies; konexin 30; dítě; Homozygote; studie případů a kontrol; Child; Connexin 26; Microsatellite Repeats; Connexins; Female; mutace; konexin 26; Hearing Loss, Sensorineural; lidé; konexiny; homozygot; delece genu; Connexin 30; Gene Deletion; ženské pohlaví; Male; Czech Republic; Heterozygote; mikrosatelitní repetice; heterozygot; Mutation; Česká republika; mužské pohlaví; percepční nedoslýchavost